Strategies of Matrimonial and Procreational Behaviour of Social Stratum: Forms and Their Change - Česnuitytė, Vida (Sociologija. Mintis ir veiksmas, 2004)
Sociological and demographical theories on matrimonial and procreational behaviour of social stratum presented in the article. Social status in relation to family formation and methods of social control in the premodern societies were discussed at the beginning. After that new forms of family formation and maintenance in the modern societies were discussed. The main conclusion of the article is that matrimonial and procreational behaviour of social stratum is on the permanent change. It changes form domination of family and community interests on individual behaviour in the premodern societies to toleration of individual behaviour in respect to family formation in the modern societies. It was stated that family formation became one of the segments of individual self-realization in the new conditions.